Trauma changes everything: Examining the relationship between adverse childhood experiences and serious, violent and chronic juvenile offenders. (August 2015) - Fox, Bryanna Hahn; Perez, Nicholas; Cass, Elizabeth; Baglivio, Michael T.; Epps, Nathan
Abstract: Among juvenile offenders, those who commit the greatest number and the most violent offenses are referred to as serious, violent, and chronic (SVC) offenders. However, current practices typically identify SVC offenders only after they have committed their prolific and costly offenses. While several studies have examined risk factors of SVCs, no screening tool has been developed to identify children at risk of SVC offending. This study aims to examine how effective the adverse childhood experiences index, a childhood trauma-based screening tool developed in the medical field, is at identifying children at higher risk of SVC offending. Data on the history of childhood trauma, abuse, neglect, criminal behavior, and other criminological risk factors for offending among 22, 575 delinquent youth referred to the Florida Department of Juvenile Justice are analyzed, with results suggesting that each additional adverse experience a child experiences increases the risk of becoming a serious, violent, and chronic juvenile offender by 35, when controlling for other risk factors for criminal behavior. These findings suggest that the ACE score could be used by practitioners as a first-line screening tool to identify children at risk of SVC offending before significant downstream wreckage occurs.